Diverse signaling mechanisms of mTOR complexes: mTORC1 and mTORC2 in forming a formidable relationship. (May 2019) - Jhanwar-Uniyal, Meena; Wainwright, John V.; Mohan, Avinash L.; Tobias, Michael E.; Murali, Raj; Gandhi, Chirag D.; Schmidt, Meic H.
Abstract: Activation of Mechanistic target of rapamycin (mTOR) signaling plays a crucial role in tumorigenesis of numerous malignancies including glioblastoma (GB). The Canonical PI3K/Akt/mTOR signaling cascade is commonly upregulated due to loss of the tumor suppressorm PTEN, a phosphatase that acts antagonistically to the kinase (PI3K) in conversion of PIP2 to PIP3. mTOR forms two multiprotein complexes, mTORC1 and mTORC2 which are composed of discrete protein binding partners to regulate cell growth, motility, and metabolism. These complexes are sensitive to distinct stimuli, as mTORC1 is sensitive to nutrients while mTORC2 is regulated via PI3K and growth factor signaling. The main function of mTORC1 is to regulate protein synthesis and cell growth through downstream molecules: 4E-BP1 (also called EIF4E-BP1) and S6K. On the other hand, mTORC2 is responsive to growth factor signaling by phosphorylating the C-terminal hydrophobic motif of some AGC kinases like Akt and SGK and it also plays a crucial role in maintenance of normal and cancer cells through its association with ribosomes, and is involved in cellular metabolic regulation. mTORC1 and mTORC2 regulate each other, as shown by the fact that Akt regulates PRAS40 phosphorylation, which disinhibits mTORC1 activity, while S6K regulates Sin1 to modulate mTORC2 activity. Allosteric inhibitors of mTOR, rapamycin and rapalogs, remained ineffective in clinical trials of Glioblastoma (GB) patients, in part due to their incomplete inhibition of mTORC1 as well as unexpected activation of mTOR via the loss of negative feedback loops. In recent years, novel ATP binding inhibitors of mTORC1 and mTORC2 suppress mTORC1 activity completely by total dephosphorylation of its downstream substrate pS6K Ser235/236, while effectively suppressing mTORC2 activity, as demonstrated by complete dephosphorylation of pAKT Ser473 . Furthermore by these novel combined mTORC1/mTORC2 inhibitors reduced the proliferation and self-renewal of GB cancer stem cells. However, a search of more effective way to target mTOR has generated a third generation inhibitor of mTOR, "Rapalink", that bivalently combines rapamycin with an ATP-binding inhibitor, which effectively abolishes the mTORC1 activity. All in all, the effectiveness of inhibitors of mTOR complexes can be judged by their ability to suppress both mTORC1/mTORC2 and their ability to impede both cell proliferation and migration along with aberrant metabolic pathways.